2019
DOI: 10.1158/2159-8290.cd-18-0715
|View full text |Cite
|
Sign up to set email alerts
|

BRCA Reversion Mutations in Circulating Tumor DNA Predict Primary and Acquired Resistance to the PARP Inhibitor Rucaparib in High-Grade Ovarian Carcinoma

Abstract: A key resistance mechanism to platinum-based chemotherapies and PARP inhibitors in BRCA-mutant cancers is the acquisition of BRCA reversion mutations that restore protein function. To estimate the prevalence of BRCA reversion mutations in high-grade ovarian carcinoma (HGOC), we performed targeted next-generation sequencing of circulating cell-free DNA (cfDNA) extracted from pretreatment and postprogression plasma in patients with deleterious germline or somatic BRCA mutations treated with the PARP inhibitor ru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
256
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(269 citation statements)
references
References 30 publications
(46 reference statements)
11
256
0
2
Order By: Relevance
“…The first example of PARP inhibitor resistance was identified in Capan-1 cells derived from a pancreatic epithelial tumour, which had an intragenic deletion in BRCA2 of 458 bp resulting in removal of the inactivating frameshift mutation and expression of an almost full-length BRCA2 protein lacking 153 amino acids (Edwards et al 2008). Since then, many examples of secondary mutations in BRCA1/2, as well as RAD51C, RAD51D, and PALB2, that genetically revert the mutation and restore functional full-length protein have been reported in breast, ovarian, pancreatic, and prostate carcinoma (Sakai et al 2008;Norquist et al 2011;Barber et al 2013;Patch et al 2015;Christie et al 2017;Goodall et al 2017;Kondrashova et al 2017;Lheureux et al 2017a;Pishvaian et al 2017;Quigley et al 2017;Weigelt et al 2017;Lin et al 2019). Platinum and cisplatin chemotherapy seem to select for these secondary mutation events (Sakai et al 2008;Norquist et al 2011).…”
Section: Restoration Of the Hr Pathwaymentioning
confidence: 99%
“…The first example of PARP inhibitor resistance was identified in Capan-1 cells derived from a pancreatic epithelial tumour, which had an intragenic deletion in BRCA2 of 458 bp resulting in removal of the inactivating frameshift mutation and expression of an almost full-length BRCA2 protein lacking 153 amino acids (Edwards et al 2008). Since then, many examples of secondary mutations in BRCA1/2, as well as RAD51C, RAD51D, and PALB2, that genetically revert the mutation and restore functional full-length protein have been reported in breast, ovarian, pancreatic, and prostate carcinoma (Sakai et al 2008;Norquist et al 2011;Barber et al 2013;Patch et al 2015;Christie et al 2017;Goodall et al 2017;Kondrashova et al 2017;Lheureux et al 2017a;Pishvaian et al 2017;Quigley et al 2017;Weigelt et al 2017;Lin et al 2019). Platinum and cisplatin chemotherapy seem to select for these secondary mutation events (Sakai et al 2008;Norquist et al 2011).…”
Section: Restoration Of the Hr Pathwaymentioning
confidence: 99%
“…This will allow much-needed large cohort studies on resistance mechanisms in patients ( Figure 2). Even though numbers are limited to date, studies have already shown that reversion mutations in BRCA1 and BRCA2 occur frequently in PARPi-resistant cancers [43,45,50,51,53,94,95]. In studies on PDX models of BRCA1-mutated tumors, concomitant loss of TP53BP1 or REV7 was identified in up to 20% of the resistant tumors [96,97].…”
Section: Resistance Mechanisms In the Clinicmentioning
confidence: 99%
“…PARP inhibitors have been approved for the treatment of BRCA1/2 mutant ovarian and breast cancers. A key mechanism of resistance to PARP inhibitors and platinum-based chemotherapy in these cancers is the acquisition of reversion mutations in BRCA1/2 that restore protein function [3,4]. Reversion mutations in BRCA2 have also been observed in a small number of mCRPC patients treated with PARP inhibitors or carboplatin [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Acquired reversion mutations in BRCA1/2 resulting from exposure to platinum chemotherapy are likely to render tumors less sensitive to PARP inhibitor treatment. In a recent study of patients with ovarian cancer treated with rucaparib following platinum, patients without BRCA1/2 reversion mutations had a significantly longer median progression-free survival than patients with reversion mutations (9.0 vs. 1.8 months; hazard ratio, 0.12; P < 0.0001) [3]. However, there are limited data on the combination or sequential use of platinum and PARP inhibitors in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%